Advances in an active and passive targeting to tumor and adipose tissues. (January 2015) - Sakurai, Yu; Kajimoto, Kazuaki; Hatakeyama, Hiroto; Harashima, Hideyoshi
<x xml:space="preserve">Abstract</x> Introduction: Data reported during the last decade of the twentieth century indicate that passive targeting is an efficient strategy for delivering nanocarrier systems to tumor tissues. The focus of this review is on active targeting as a next-generation strategy for extending the capacity of a drug delivery system (DDS). Areas covered: Tumor vasculature targeting was achieved using arginine- glycine-aspartic acid, asparagine-glycine-arginine and other peptides, which are well-known peptides, as ligand against tumor vasculature. An efficient system for delivering small interfering RNA to the tumor vasculature involved the use of a multifunctional envelope-type nanodevice based on a pH-modified cationic lipid and targeting ligands. The active-targeting system was extended from tumor delivery to adipose tissue delivery, where endothelial cells are tightly linked and are impermeable to nanocarriers. In mice, prohibitin-targeted nanoparticles can be used to successfully deliver macromolecules to induce anti-obese effects. Finally, the successful delivery of nanocarriers to adipose tissue in obese mice via the enhanced permeability and retention-effect is reported, which can be achieved in tumor tissue. Expert opinion: Unlike tumor tissues, only a few reports have appeared on how liposomal carriers accumulate in adipose tissues after systemic injection. This finding, as well as active targeting to the adipose vasculature, promises to extend the capacity of DDS to adipose tissue. Since the site of action of nucleic acids is the cytosol, the intracellular trafficking of carriers and their cargoes as well as cellular uptake must be taken into consideration.